Про особливості дослідження незв’язаних збуджених станів ядра 4He в α + 3H взаємодії - Povoroznyk, O.M.; Gorpinich, O.K.; Ponkratenko, O.A. (Publishing house "Academperiodika", 2023)
Due to the alpha-particle beam interaction with tritium, the two-dimensional spectra of tt, t3He, and dd coincidences are obtained using the particle-decay spectroscopy from three-particle 3H(α,tt)p, 3H(α,t 3He)n, and 3H(α,td)d reactions (Eα = 67.2 MeV). Excitation energies and energy widths for seven excited 4He states, as well as the ratio of their different decay modes, namely t + p, n + 3He, and d + d, are obtained by using the Monte Carlo method.